Phenomenology: comprehensive and Interpretative philosophy for Nursing Care - Acevedo-Figueroa, Lucila (Universidad de Sonora, 2019)
Introduction: In nursing, thinking serves to discover or rediscover the sense of what we call concept; procedure, serves to establish what is phenomenologically manifested when searching the essence of form. To reflect on phenomenological perspective in the process of care affects both fulfillment and significant nursing practice. Objective: Presenting phenomenological philosophy through a comprehensive and interpretative healthcare perspective that describes the importance of its inclusion in the nursing care practice towards the comprehension of being. Development: Understanding the ailing person in full human dimension via reflective analysis, provides an established way to understand reality, delving more deeply into the internal sphere of things in order to appreciate their true being, leaving the external aside. The obvious, which begins with cause and effect, possesses a scientific structure to both interpret and comprehend the subjectivity of thought, discovering essential structures of conscience and establishing the social responsibility of nursing for the development of potentialities, capacities, and possibilities of the well-being of individuals and communities. Conclusions: Endless are the roads of nursing care. Presenting phenomenological philosophy provides tools to understand what human beings are able to establish within their environment during their search for health, based on a greater understanding about human existence and about being a nurse.